Development of copper based miniature electrostatic actuator using WEDM with low actuation voltage - Bhuiyan, Moinul; Shihab, Baten (Springer, 2014)
Fabricating electrostatic micro actuator, such as comb-drive actuator, is one of the demanding areas of the MEMS technology because of the promising applications in modern engineering, such as, micro-switches, attenuators, filters, micro-lenses, optical waveguide couplers, modulation, interferometer, dynamic focus mirror, and chopper. For the fabrication, most of the cases silicon monocrystalline wafers are used through complex process. To etch the silicon substrates, researchers often use deep reactive-ion etching or anisotropic wet etching procedure which are time consuming and unsuitable for batch fabrication process. Again, resent research shows that comb-drive actuators need comparatively high voltage for actuation. In solving these problems, the study presents a copper based electrostatic micro actuator with low actuation voltage. Using wire electrical discharge machine (WEDM), the actuator is fabricated where a light weight flexible spring model is introduced. Capacitor design model is applied to present a voltage controlling electronic circuit using Arduino micro controller unit. The experimental result shows that the actuator is able to produce 1.38 mN force for 15 V DC. The experiment also proves that coper based actuator design using WEDM technology is much easier for batch processing and could provide the advantages in rapid prototyping.